Development of Indoor Aquaponic System with Monitoring Mechanism for Tilapia and Pak Choy - Amri, Asri; Sari, Suhaila; Yusoff, Amri; Roslan, Hazli; Ibrahim, Nabilah; Mohd Muji, Siti Zarina (Evolution in Electrical and Electronic Engineering, 2022)
This study aimed to create a smart aquaponics system that could manage and monitor PH, total dissolved solids (TDS), turbidity, water level, oxygen (ORP), and temperature levels. The quality of the water is checked throughout the day with this system, and the user will change the water or add the water depending on the changes. Each of the sensors has its role in order to stabilize the water condition. For example, Tilapia can survive below the PH value of 5.5 and Pak Choy is suitable for a PH value of 6.5. There are 3 objectives in these studies, which are to develop an aquaponic system for the indoor environment specifically for Tilapia and Pak Choy, to develop a monitoring mechanism for the aquaponic system and to analyse the performance of the developed system. The proposed aquaponic system has 8 different results which are the weight of the fish, plant growth and the 6 sensors reading that enables the user to find the relationship of each reading. From the reading, the FCR reading is 1.5949 where the value of FCR has been reached which is more than 1. Growth recording rate reaches 4.62, survival and condition factor reach 100% for survival rate and condition factor is 32.73, mortality rate stays 0 and length gain of tilapia is 2.5cm and Pak Choy is 3.5cm after taking the reading of 9 weeks. All of this reading proves that the project has finally succeeded in all aspects.